Current suicidality and previous suicidal attempts in patients with schizophrenia are associated with different dimensions of temperament and character - Aukst-Margetić, Branka (Array, 2012)
Suicide is a major public health problem and the leading cause of premature death in patients with schizophrenia. Information about the patient’s personality is helpful for assessing the risk of suicide attempts and suicidal ideation. The sample consisted of 120 outpatients with a diagnosis of schizophrenia, 29 of whom had previously attempted suicide. We used the Temperament and Character Inventory to assess personality differences between patients who had previously attempted and had not previously attempted suicide and between patients who had and did not have current suicidal ideation. Current suicidal ideation was assessed using the four-point severity scale, which is item nine from the Beck Depression Inventory. The character dimension Self-transcendence was shown by logistic regression to be a predictor of lifetime suicide attempts. Low Self-directedness was shown to be a predictor of current suicidal ideation. To prevent suicidal behaviour, it is important to better understand the personality traits associated with suicidal ideation and suicide attempts. Suicide attempts and suicidal ideation in schizophrenia may not represent the same phenomenon ranging on a single continuum. The importance of these results suggests that further study is needed.